Policy analysis of the ISPA control program for toddlers in the working area of the Ngegong Health Center in Madiun City - Arissa Yolanda Priyanti; Retno Widiarini; Pipid Ari Wibowo (International Journal of Health Literacy and Science, 2023)
ARI is an infectious disease that causes the main cause of death in the world, especially in infants and children. In the Ngegong Community Health Center working area, in 2021 there were 957 ISPA cases recorded, and in 2022 this increased to 2288 cases with a total of 125 ISPA cases in toddlers in 2021-2022, which is still relatively high. The research used qualitative methods, carried out at the Ngegong Community Health Center, Madiun City from June to July 2023. The informants were determined using purposive sampling. Primary data was obtained from the results of in-depth interview texts, document review, and observations with informants. The data obtained was analyzed qualitatively and described descriptively. The research results showed that nursing staff, funds were still included in the program in general, facilities and infrastructure were available, planning was carried out at the same UKP cadre and pramin refresher meeting, but there was no evidence of minutes, organization was already in place and those involved were midwives, nurses and doctor, there is an approach through the village head, monitoring the ISPA evaluation at the Puskesmas in the form of a visit by the health service and a report is made. The P2ISPA activity program at the Health Center is reported by the person in charge every month. It was concluded that the ISPA control program at the Ngegong Community Health Center in Madiun City had not been effective. It is hoped that Health Center will prioritize controlling ISPA by increasing the public's understanding (mothers of toddlers) about ISPA on an ongoing basis, and the management and eradication of ISPA cases that have been implemented is expected to be further improved.